2012
DOI: 10.1177/0273475312450388
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Team-Based Learning as an Approach to Increased Engagement and Learning for Marketing Students

Abstract: Marketing educators are often faced with poor preclass preparation by students, declining student interest in attending classes as the semester progresses, and student complaints regarding previous bad experiences with team assessment activities. Team-based learning (TBL) is an innovative teaching strategy using semiformalized guidelines aimed to enhance student engagement and improve teamwork and, hence, overcome the typical problems faced by educators. This case study examines the first-time use of TBL in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 58 publications
4
39
0
1
Order By: Relevance
“…Making evidence-based judgements and sound clinical decisions are natural evolutionary outcomes of a learning process that demands rationale and justification at every iteration. Indeed, students' abilities to think effectively are significantly enhanced by the emphasis on facilitating thinking skills in a team context where students learn how to incorporate others' views, ideas and perspectives and deal with the challenges of differences and concepts not fully grasped before attending class (Chad, 2012).…”
Section: Tbl Is Helping the Way We Think [Tbl Is A ] Better Way Of Lementioning
confidence: 99%
“…Making evidence-based judgements and sound clinical decisions are natural evolutionary outcomes of a learning process that demands rationale and justification at every iteration. Indeed, students' abilities to think effectively are significantly enhanced by the emphasis on facilitating thinking skills in a team context where students learn how to incorporate others' views, ideas and perspectives and deal with the challenges of differences and concepts not fully grasped before attending class (Chad, 2012).…”
Section: Tbl Is Helping the Way We Think [Tbl Is A ] Better Way Of Lementioning
confidence: 99%
“…The authors found that students generally rated TBL positively and recognised its benefits to develop teamwork skills. A similar study was conducted by Chad (2012) who examined the first time use of TBL in a postgraduate marketing module in an Australia university. The author found that TBL had a positive influence on student engagement and offered opportunities for assisted learning.…”
Section: Background For the Studymentioning
confidence: 96%
“…Frame et al, 2015;Reinig et al, 2011;Cho et al, 2010), with fewer studies focusing on qualitative data (e.g. Sutherland et al, 2013;Chad, 2012). In addition to this, there is scant research on the challenges faced by instructors during TBL courses.…”
Section: Background For the Studymentioning
confidence: 99%
“…Hernandez (2002), however, also places this type of active and applied learning firmly in the realm of helping students to build important graduate capabilities, asserting that today's employers 'need employees who can apply what they have learned and who can analyze, evaluate, and find solutions to problems' (p. 74). Chad (2012), similarly focuses on the use of TBL as a way to help students to develop skills that are highly valued in the workplace, in particular the ability to work effectively with each other repeatedly on team-based activities. Similarly, after a significant literature review of over 130 articles on TBL, Haidet, Kubitz, and McCormack (2014), found growing empirical literature that supports the assertions that 'Team-based learning helps bring up students at the bottom of the curve'; 'Team-based learning creates lots of excitement and engagement in the classroom, and that energizes me and my teaching'; and 'My students are better prepared to work in teams as a result of my using teambased learning,' (Haidet et al, 2014, p. 312).…”
Section: Team-based Learning As a Strategic Responsementioning
confidence: 99%